INSTRUCTIONAL DESIGN: A LEARNING STRATEGY APPLIED TO NURSING HISTORY IN REMOTE TEACHING - Pacita Geovana Gama de Sousa Aperibense; Bruna Tavares Uchoa dos Santos Xavier; Rafael Lustosa Ribeiro; Valeria Aparecida Masson; Marco Antonio Carvalho Filho (Cogitare Enfermagem, 2022)
Objective: to describe the elaboration of a virtual learning object to teach the Nursing History academic discipline.